STUDI KORELASI ANTARA LINGKUNGAN DAN AKTIVITAS BELAJAR DENGAN PRESTASI BELAJAR DALAM PEMBELAJARAN BAHASA ARAB - Nur Fadilah Amin (Universitas Muhammadiyah Makassar, 2017)
This study aims to determine the correlation between the environment and learning activities with learning achievement in a process of learning Arabic students of VIII class in MTs Muhammadiyah Kampung Baru Bulukumba. The method used to collect research data was observation, questionnaires, documentation and interviews. The results of this study indicated that there was a correlation between the environment and learning activities to the level of learning achievement of Arabic students of VIII class in MTs Muhammadiyah Kampung Baru Bulukumba. Judging from the calculation of learning environment with learning activity, the result of signification is 0,212 0,05 with rhitung rtabel (at 5% = 0,392 and 1% = 0,515), that is; 0.553 0.392 / 0.515. Between learning environment with learning achievement seen from result of significance equal to 0,395 0,05 with rhitung rtabel (at 5% = 0,392 and 1% = 0,515), that is; 0.574 0.392 / 0.515. And there was a significant relationship between learning activities with learning achievement. Seen from the signification result of 0.335 0,05 with rhitung rtabel (at 5% = 0,392 and 1% = 0,515), that is; 0.697 0.392 / 0.515. Keywords: correlation, environment, activity, achievement